Analyzing the Dynamics of Double Movement in Water Resource Conflicts: A Critical Examination of Umbul Gemulo Spring in Batu City - Achmadinata, Raihan Rakha Dhiya; Fahadayna, Adhi C.; Azis, Aswin Ariyanto (Universitas Muhammadiyah Tangerang, 2025)
This study examines the resistance of Umbul Gemulo residents to the construction of The Rayja Hotel in Batu City, East Java, through the lens of Karl Polanyi's concept of the